Intestinal immunoglobulins under microbial dysbiosis: implications in opioid-induced microbial dysbiosis - Nicolas Vitari; Nicolas Vitari; Sabita Roy; Sabita Roy (Frontiers in Microbiology)
Intestinal immunoglobulins (Igs) maintain homeostasis between the microbiome and host. IgA facilitates microbial balance through a variety of increasingly well-described mechanisms. However, IgM and IgG have less defined intestinal functions but have the potential to activate clearance mechanisms such as the complement system and receptor-mediated bacterial killing. Very little is known regarding the role of Igs under microbial dysbiosis. In this review, we explore how Igs sculpt the intestinal microbiome and respond to microbial dysbiosis. We discuss how IgM, IgA, IgG, and complement individually maintain harmony with the microbiome and consider how these mechanisms could work in synergy. Finally, we explore using an opioid-induced microbial dysbiosis as a model to elucidate immediate changes in Ig-bacterial interactions.